Proton capture reactions on 116Sn and 118Sn relevant to the p process - Spyrou, A.; Lagoyannis, A.; Zarkadas, Ch.; Perdikakis, G.; Galanopoulos, S.; Demetriou, P.; Harissopulos, S.; Fey, M.; Kunz, R.; Hammer, J. W.; Becker Η. W.; Rolfs, C. (HNPS Advances in Nuclear Physics, 2019)
The proton capture reaction cross sections on 116Sn and 118Sn have been determined at astrophysically relevant energies by means of activation, 7-ray angular distribution and angle-integrated 7-flux measurements. The results of the present work together with those obtained in previous measurements are compared to the predictions of the Hauser-Feshbach theory.